A conceptual framework of tax compliance intention among individuals in Gig economy - Mohaneswari Renganathan; Junainah Jaidi (Faculty of Business, Economics and Accountancy, 2021)
This paper aims to utilise a conceptual framework of theory of reasoned action (TRA) that can be used to analyse and discuss factors influencing tax compliance intention of individuals in digital (gig) economy in Malaysia. Gig economy is a term used to refer to an economy activity based on the use of digital technology. TRA asserts the components to behaviour: attitude and subjective norms. Based on the components, the determinants are developed to study tax compliance intention: taxpayer morale and trust in government. The paper provides new insights on tax compliance studies by introducing the concept of digital business that is increasingly becoming a popular segment of the economy, especially among the younger generation. This would be useful for the government to establish a clear tax framework in promoting digital economy to broaden the tax base for the government.